The Changing Impact of Snow Conditions and Refreezing on the Mass Balance of an Idealized Svalbard Glacier - van Pelt, Ward J. J.; Pohjola, Veijo A.; Reijmer, Carleen H. (Frontiers in Earth Science, 2016)
Glacier surface melt and runoff depend strongly on seasonal and perennial snow (firn) conditions. Not only does the presence of snow and firn directly affect melt rates by reflecting solar radiation, it may also act as a buffer against mass loss by storing melt water in refrozen or liquid form. In Svalbard, ongoing and projected amplified climate change with respect to the global mean change has severe implications for the state of snow and firn and its impact on glacier mass loss. Model experiments with a coupled surface energy balance - ﬁrn model were done to investigate the surface mass balance and the changing role of snow and ﬁrn conditions for an idealized Svalbard glacier. A climate forcing for the past, present and future (1984-2104) is constructed, based on observational data from Svalbard Airport and a seasonally dependent projection scenario. Results illustrate ongoing and future ﬁrn degradation in response to an elevational retreat of the equilibrium line altitude (ELA) of 31 m decade−1. The temperate ﬁrn zone is found to retreat and expand, while cold ice in the ablation zone warms considerably. In response to pronounced winter warming and an associated increase in winter rainfall, the current prevalence of refreezing during the melt season gradually shifts to the winter season in a future climate. Sensitivity tests reveal that in a present and future climate the density and thermodynamic structure of Svalbard glaciers are heavily inﬂuenced by refreezing. Refreezing acts as a net buffer against mass loss. However, the net mass balance change after refreezing is substantially smaller than the amount of refreezing itself, which can be ascribed to melt-enhancing effects after refreezing, which partly offset the primary mass-retaining effect of refreezing.